Strategi Komunikasi Pemasaran Dalam Menangani Komplain Konsumen Produk Jam Tangan/Arloji Melalui Media Sosial : Studi PT Optima Technology Indonesia Pada Tiktok - Hendro, Hendro (Brand Communication, 2024)
The advancement of digital technology has significantly impacted daily life. The widespread utilization of social media has facilitated ease of access for industry stakeholders to identify and address customer complaints or grievances. TikTok, among other platforms, serves as a channel through which customers articulate their concerns. The objective of this study is to examine the marketing communication strategies employed by PT Optima Technology Indonesia in addressing consumer complaints on the social media platform TikTok. It will specifically focus on customer happiness, loyalty, and the factors that influence them. The study, which employed qualitative methodologies including as interviews with Customer service and E-commerce specialists, reveals that PT Optima Technology Indonesia’s marketing communication efforts are generally seen favourably. Nevertheless, the research provides suggestions to PT Optima Technology Indonesia on how to improve the quality of their products and services, specifically in dealing with product complaints on TikTok. The findings indicate that PT Optima Technology Indonesia can enhance the quality of its products and services by comprehending the specific attributes of complaints or grievances stated by customers in a blunt manner on TikTok. Moreover, the study emphasises the significance of PT Optima Technology Indonesia in identifying areas that need improvement and devising communication strategies based on these findings.